2022
DOI: 10.1038/s12276-022-00851-8
|View full text |Cite
|
Sign up to set email alerts
|

Metabolic improvement and liver regeneration by inhibiting CXXC5 function for non-alcoholic steatohepatitis treatment

Abstract: Non-alcoholic steatohepatitis (NASH) is a chronic liver disease that results from multiple metabolic disorders. Considering the complexity of the pathogenesis, the identification of a factor mediating the multiple pathogenic phenotypes of NASH will be important for treatment. In this study, we found that CXXC5, a negative feedback regulator of the Wnt/β-catenin pathway, was overexpressed with suppression of Wnt/β-catenin signaling and its target genes involved in hepatic metabolism in obese-NASH patients. Cxxc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
6
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4

Relationship

2
2

Authors

Journals

citations
Cited by 4 publications
(6 citation statements)
references
References 44 publications
0
6
0
Order By: Relevance
“… 109 Seo et al. 110 T3, TRβ and SNHG12 accelerated hepatocyte proliferation and LR by regulating Wnt/β-catenin signaling. Hönes et al.…”
Section: Signaling Pathways In Lrmentioning
confidence: 99%
See 1 more Smart Citation
“… 109 Seo et al. 110 T3, TRβ and SNHG12 accelerated hepatocyte proliferation and LR by regulating Wnt/β-catenin signaling. Hönes et al.…”
Section: Signaling Pathways In Lrmentioning
confidence: 99%
“…also proved that activating or enhancing Wnt/β-catenin pathway promoted LR. 108 , 109 , 110 Other studies have also demonstrated that certain genes act as the regulators of Wnt/β-catenin pathway, which accelerates hepatocyte growth and LR by regulating Wnt/β-catenin pathway. 111 , 112 Yin and Clemens et al.…”
Section: Signaling Pathways In Lrmentioning
confidence: 99%
“…In the cytosol, CXXC5 is a negative regulator of Wnt/β-catenin signaling, and it functions by interacting with the upstream component Dishevelled (Dvl) 18,19 . Cytosolic CXXC5 accumulation has been observed in several diseases, such as osteoporosis, alopecia, and metabolic diseases, and is accompanied by impaired regeneration of damaged tissues [19][20][21][22][23] . Protein transduction domain-fused Dishevelled binding motif (PTD-DBM) peptide, which interferes with the CXXC5-Dvl protein-protein interaction (PPI), promotes cutaneous wound healing and neogenic hair growth through the restoration of Wnt/β-catenin signaling 19,24 .…”
Section: Introductionmentioning
confidence: 99%
“…Protein transduction domain-fused Dishevelled binding motif (PTD-DBM) peptide, which interferes with the CXXC5-Dvl protein-protein interaction (PPI), promotes cutaneous wound healing and neogenic hair growth through the restoration of Wnt/β-catenin signaling 19,24 . In addition, small molecular mimetics of PTD-DBM peptide that interferes the function of CXXC5, such as KY19382 and KY19334, induce wound healing, hair growth, and longitudinal bone growth, and improve metabolic abnormalities, including diabetes, by activating Wnt/β-catenin signaling 19,20,[22][23][24] . The effectiveness of small molecules that interfere with the function of cytosolic CXXC5 further confirmed the CXXC5-Dvl PPI as a target for treating diseases with suppressed Wnt/β-catenin signaling, such as baldness, bone growth senescence, and metabolic diseases such as obese type 2 diabetes and nonalcoholic steatohepatitis [20][21][22][23] .…”
Section: Introductionmentioning
confidence: 99%
“…CXXC5 plays various pathophysiological roles involving adult tissue regeneration at the specific pathophysiological status [13][14][15][16] . Growing evidence indicates that CXXC5 is a key driving factor for metabolic diseases 17 and inhibition of CXXC5 function accelerates liver tissue regeneration with metabolic improvements 18 . Thus we reasoned that CXXC5 might be highly expressed with suppression of Wnt/βcatenin signaling in the early adipogenic differentiation during the development of obesity.…”
mentioning
confidence: 99%